2022
DOI: 10.1177/09567976221108941
|View full text |Cite
|
Sign up to set email alerts
|

Early Impacts of College, Interrupted: Considering First-Year Students’ Narratives About COVID and Reports of Adjustment During College Shutdowns

Abstract: The COVID-19 pandemic has threatened lives and livelihoods, imperiled families and communities, and disrupted developmental milestones globally. Among the critical developmental disruptions experienced is the transition to college, which is common and foundational for personal and social exploration. During college shutdowns (spring 2020), we recruited 633 first-year U.S. students (mean age = 18.83 years, 71.3% cisgender women) to provide narratives about the impacts of the pandemic. We tested the ways narrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Conversely, ED patients reported more psychologically severe effects of the COVID-19 crisis after 2 years than after 1 year. This evidence aligns with recent evidence of changes in autobiographical memories over time in individuals with traumatic histories (Booker et al 2022 ). In fact, coherence, details, and interpretation could require time, with implications for awareness of symptoms and behaviors that require a specific focus (Booker et al 2020 ; Fivush et al 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, ED patients reported more psychologically severe effects of the COVID-19 crisis after 2 years than after 1 year. This evidence aligns with recent evidence of changes in autobiographical memories over time in individuals with traumatic histories (Booker et al 2022 ). In fact, coherence, details, and interpretation could require time, with implications for awareness of symptoms and behaviors that require a specific focus (Booker et al 2020 ; Fivush et al 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…In research on trauma and resilience in college students, the process of making sense and integrating it into stories and ideas about oneself is a valuable coping strategy [ 51 ]. To this end, some young people during the pandemic formed stories about challenges leading to personal growth, maturation, and sense of purpose that were linked with psychosocial adjustment, identity development, and resilience [ 44 , 52 , 53 ]. Importantly, such sense-making can be facilitated by social systems and supports.…”
Section: Resilience Coping and Meaningmentioning
confidence: 99%
“…Empirical investigations of psychological resilience and college adjustment frequently rely heavily on the total condition. However, previous research has found that resilience in college adjustment is not monolithic but person‐specific (Booker et al, 2022). Via LPA, college adjustment could significantly differ in four psychological resilience subgroups in China.…”
Section: Introductionmentioning
confidence: 96%